2010
DOI: 10.1007/s11104-010-0394-2
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of fire on soil and plant nutrients in palmetto flatwoods

Abstract: Fire may have different effects on the relative availability of nitrogen (N) and phosphorus (P) because N volatilization occurs at lower temperatures than P volatilization, and fire-mediated changes in soil nutrient availability may affect foliar nutrient concentrations. We assessed the short-term effects of fire on soil and plant nutrients and 15 N isotopic signatures in a palmetto flatwoods ecosystem in central Florida. Fire caused a short-term increase in extractable ammonium (NH 4 + ) and phosphate (PO 4 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 99 publications
(128 reference statements)
3
47
0
Order By: Relevance
“…5). Although a global meta-analysis found that post-fire soil NO − 3 concentrations peak 10 months after NH + 4 concentrations (Wan et al, 2001), studies in southeastern US ecosystems found no change in soil NO − 3 up to 30 days (pine savanna; Boring et al, 2004), 320 days (pine forest; Lavoie et al, 2010) and 500 days (shrubland; Schafer and Mack, 2010) following fire. Across the full growing season, we measured NH + 4 pool sizes of burned sites that were nearly 5 times that of unburned sites.…”
Section: Changes In N Dynamics Across the Growing Seasonmentioning
confidence: 98%
See 2 more Smart Citations
“…5). Although a global meta-analysis found that post-fire soil NO − 3 concentrations peak 10 months after NH + 4 concentrations (Wan et al, 2001), studies in southeastern US ecosystems found no change in soil NO − 3 up to 30 days (pine savanna; Boring et al, 2004), 320 days (pine forest; Lavoie et al, 2010) and 500 days (shrubland; Schafer and Mack, 2010) following fire. Across the full growing season, we measured NH + 4 pool sizes of burned sites that were nearly 5 times that of unburned sites.…”
Section: Changes In N Dynamics Across the Growing Seasonmentioning
confidence: 98%
“…Fire may stimulate microbial turnover of organic matter if additions of C or N from ash deposition or root exudation (southern shrubland; Schafer and Mack, 2010) enhance microbial activity. Soil surface blackening after fire may increase soil temperature and stimulate immediate and prolonged N transformations after fire (Booth et al, 2005;Ojima et al, 1994).…”
Section: Assessing Mechanisms Of N Pulses Following Firementioning
confidence: 99%
See 1 more Smart Citation
“…Fire induced pH changes may last for over 3 years after burning (Ulery et al, 1993), nearly long enough to begin accumulating available P in the 5-year-interval treatments. Schafer and Mack (2010) found that the effects of burning on available P were longer lasting than available N suggesting that the effects of burning on available P may accumulate when sites are reburned if the burning interval is short enough.…”
Section: Available Nutrientsmentioning
confidence: 99%
“…While considerable knowledge has accumulated about plant-soil relationships, these mostly encompass single-species studies (Morales-Sillero et al 2009;Schafer and Mack 2010). Less is known about vegetation-soil interactions and about how vegetation status, including degradation is reflected in soils.…”
Section: Introductionmentioning
confidence: 99%